2018
DOI: 10.3390/catal8100453
|View full text |Cite
|
Sign up to set email alerts
|

SnO2 Composite Films for Enhanced Photocatalytic Activities

Abstract: As a new type of promising semiconductor photocatalyst, SnO2 cannot be widely applied due to its low utilization efficiency to visible light and swift recombination of photogenerated electrons and holes. These drawbacks were effectively overcome by preparing the B/Ag/F tridoped SnO2-ZnO composite films using the simple sol–gel method. The degradation of the methyl green and formaldehyde solutions was used to value the photocatalytic activity of the samples. Photoluminescence (PL) spectra and the UV–Vis absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Rotatable (PSP) system with (On/ Off-mode) keeps the substrate temperature constant which promote the adhesion between the substrate and the deposited layers, permits enough time for film growth and homogeneity improvement. The substrate / nozzle distance isfixed at 30 cm with a solution flow rate of 5 ml / 2 min during different spray times (5,10,15 The structural properties of the deposited samples are examined by Grazing angle X-ray diffraction technique (GAXRD -Diano corroboration-USA equipment with Cu K α radiation of λ= 1.514 Å) to clarify the structure, crystallite size and to recognize the appeared phases of the investigated samples. The surface topography and film thickness are explored by scanning electron microscopy (SEM).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rotatable (PSP) system with (On/ Off-mode) keeps the substrate temperature constant which promote the adhesion between the substrate and the deposited layers, permits enough time for film growth and homogeneity improvement. The substrate / nozzle distance isfixed at 30 cm with a solution flow rate of 5 ml / 2 min during different spray times (5,10,15 The structural properties of the deposited samples are examined by Grazing angle X-ray diffraction technique (GAXRD -Diano corroboration-USA equipment with Cu K α radiation of λ= 1.514 Å) to clarify the structure, crystallite size and to recognize the appeared phases of the investigated samples. The surface topography and film thickness are explored by scanning electron microscopy (SEM).…”
Section: Methodsmentioning
confidence: 99%
“…Optical measurements (transmittance and reflectance spectra) are performed by double beam spectrophotometer (JASCO-670 UV-VIS-NIR) in wavelength range from 0.2 to 2.5 µm. ZnO film deposited at 500 o C and a spray time of 25 min is selected for selective etching by immersing the ZnO supported glass substrate in much diluted potassium hydroxide (KOH) solution of 50 mM for 5 minutes in water bath at 80 o C. This chemical etching process is widely used because it is simple and efficient way to change the surface morphology of thin film structure [5,6].Then, photocatalytic activities are evaluated for the etched and non-etched ZnO samples. Photodegradation test was executed by immersing both of the etched [6] and non-etched ZnO thin films into 5 ml of MB [C 16 H 18 ClN 3 S] aqueous solution (10 mg/L) under illumination by a UVpen lamp (λ max = 254 nm and power 5 mW/cm 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we prepared 0.02 mol/L NaOH ethanol solution (B solution) by dissolving 0.008 g NaOH in 10 mL absolute ethanol. Lastly, in a volume ratio of 1/9, we added B solution to A solution with stirring for half an hour [23]. After three days aging, ZnO sol would be obtained.…”
Section: Film Preparationmentioning
confidence: 99%
“…Han et. al [10] found that B/Ag/F tridoped SnO2-ZnO film is attributed to the low recombination rate of electron-hole pairs. The C-N-S doped TiO2 was observed for the highest photocatalytic activity for Rhodamine B degradation under visible illumination irradiation [11].…”
Section: Introductionmentioning
confidence: 99%